The Phytohormone Ethylene Enhances Cellulose Production, Regulates CRP/FNRKx Transcription and Causes Differential Gene Expression within the Bacterial Cellulose Synthesis Operon of Komagataeibacter (Gluconacetobacter) xylinus ATCC 53582 - Augimeri, Richard V.; Strap, Janice L. (Frontiers in Microbiology, 2015)
Komagataeibacter (formerly Gluconacetobacter) xylinus ATCC 53582 is a plant-associated model organism for bacterial cellulose (BC) biosynthesis. This bacterium inhabits the carposphere where it interacts with fruit through the bi-directional transfer of phytohormones. The majority of research regarding K. xylinus has been focused on identifying and characterizing structural and regulatory factors that control BC biosynthesis, but its ecophysiology has been generally overlooked. Ethylene is a phytohormone that regulates plant development in a variety of ways, but is most commonly known for its positive role on fruit ripening. In this study, we utilized ethephon (2-chloroethylphosphonic acid) to produce in situ ethylene to investigate the effects of this phytohormone on BC production and the expression of genes known to be involved in K. xylinus BC biosynthesis (bcsA, bcsB, bcsC, bcsD, cmcAx, ccpAx and bglAx). Using pellicle assays and reverse transcription quantitative polymerase chain reaction (RT-qPCR), we demonstrate that ethephon-derived ethylene enhances BC directly in K. xylinus by up-regulating the expression of bcsA and bcsB, and indirectly though the up-regulation of cmcAx, ccpAx and bglAx. We confirm that IAA directly decreases BC biosynthesis by showing that IAA down-regulates bcsA expression. Similarly, we confirm that ABA indirectly influences BC biosynthesis by showing it does not affect the expression of bcs operon genes. In addition, we are the first to report the ethylene and indole-3-acetic acid (IAA) induced differential expression of genes within the bacterial cellulose synthesis (bcs) operon. Using bioinformatics we have identified a novel phytohormone-regulated CRP/FNRKx transcription factor and provide evidence that it influences BC biosynthesis in K. xylinus. Lastly, utilizing current and previous data, we propose a model for the phytohormone-mediated fruit-bacteria interactions that K. xylinus experiences in nature.